Risk-Factors for Exposure Associated With SARS-CoV-2 Detection After Recent Known or Potential COVID-19 Exposures Among Patients Seeking Medical Care at a Large Urban, Public Hospital in Fulton County, Georgia - A Cross-Sectional Investigation - Sarah E. Smith-Jeffcoat; Sadia Sleweon; Mitsuki Koh; George M. Khalil; Marcos C. Schechter; Marcos C. Schechter; Paulina A. Rebolledo; Paulina A. Rebolledo; Vyjayanti Kasinathan; Vyjayanti Kasinathan; Adam Hoffman; Adam Hoffman; et al. (Frontiers Media S.A., 2022)
We aimed to describe frequency of COVID-19 exposure risk factors among patients presenting for medical care at an urban, public hospital serving mostly uninsured/Medicare/Medicaid clients and risk factors associated with SARS-CoV-2 infection. Consenting, adult patients seeking care at a public hospital from August to November 2020 were enrolled in this cross-sectional investigation. Saliva, anterior nasal and nasopharyngeal swabs were collected and tested for SARS-CoV-2 using RT-PCR. Participant demographics, close contact, and activities ≤14 days prior to enrollment were collected through interview. Logistic regression was used to identify risk factors associated with testing positive for SARS-CoV-2. Among 1,078 participants, 51.8% were male, 57.0% were aged ≥50 years, 81.3% were non-Hispanic Black, and 7.6% had positive SARS-CoV-2 tests. Only 2.7% reported COVID-19 close contact ≤14 days before enrollment; this group had 6.79 adjusted odds of testing positive (95%CI = 2.78-16.62) than those without a reported exposure. Among participants who did not report COVID-19 close contact, working in proximity to ≥10 people (adjusted OR = 2.17; 95%CI = 1.03-4.55), choir practice (adjusted OR = 11.85; 95%CI = 1.44-97.91), traveling on a plane (adjusted OR = 5.78; 95%CI = 1.70-19.68), and not participating in an essential indoor activity (i.e., grocery shopping, public transit use, or visiting a healthcare facility; adjusted OR = 2.15; 95%CI = 1.07-4.30) were associated with increased odds of testing positive. Among this population of mostly Black, non-Hispanic participants seeking care at a public hospital, we found several activities associated with testing positive for SARS-CoV-2 infection in addition to close contact with a case. Understanding high-risk activities for SARS-CoV-2 infection among different communities is important for issuing awareness and prevention strategies.